2012
DOI: 10.1038/tp.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of expression of schizophrenia susceptibility genes in the primate hippocampal formation

Abstract: The hippocampal formation is essential for normal memory function and is implicated in many neurodevelopmental, neurodegenerative and neuropsychiatric disorders. In particular, abnormalities in hippocampal structure and function have been identified in schizophrenic subjects. Schizophrenia has a strong polygenic component, but the role of numerous susceptibility genes in normal brain development and function has yet to be investigated. Here we described the expression of schizophrenia susceptibility genes in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…4), suggesting the disease mechanism of SCZ with different subtypes may have the same pathways. Our results were consistent with the previous findings that most susceptibility genes associated with SCZ were functional in neuron [O'Dushlaine et al, 2011;Kahler et al, 2008;Favre et al, 2012]. In addition, our results further implicated that these 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 neuron related genes might also affect SCZ development through DNA methylation aberration except for the genetic way.…”
Section: Neuron System Related Genes Were Enriched In the Hypermethylsupporting
confidence: 95%
“…4), suggesting the disease mechanism of SCZ with different subtypes may have the same pathways. Our results were consistent with the previous findings that most susceptibility genes associated with SCZ were functional in neuron [O'Dushlaine et al, 2011;Kahler et al, 2008;Favre et al, 2012]. In addition, our results further implicated that these 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 neuron related genes might also affect SCZ development through DNA methylation aberration except for the genetic way.…”
Section: Neuron System Related Genes Were Enriched In the Hypermethylsupporting
confidence: 95%
“…Taken together, these data indicate that the topographical organization of the primate hippocampal formation circuitry is established by birth, but that there is continued refinement of many aspects of hippocampal connectivity, at least for many months after birth (Favre et al, ; Jabes et al, , ; Lavenex et al, ). Accumulating evidence suggests that the differential maturation of distinct hippocampal circuits contributes to the emergence of different “hippocampus‐dependent” memory processes over the course of postnatal development (Lavenex and Lavenex Banta, ).…”
Section: Discussionmentioning
confidence: 86%
“…Accumulating evidence suggests that the differential maturation of distinct hippocampal circuits contributes to the emergence of different “hippocampus‐dependent” memory processes over the course of postnatal development (Lavenex and Lavenex Banta, ). Thus, factors that affect hippocampal development at any point during this period could have serious consequences for normal cognitive development (Ribordy et al, ) and for the emergence of neurodevelopmental conditions such as schizophrenia (Favre et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is now well established that the hippocampal formation is not a single structure, but comprises a number of distinct regions and circuits Lavenex & Amaral, 2000) that subserve different computational processes and memory functions (Copara et al, 2014;Kesner, Lee, & Gilbert, 2004;Nakashiba et al, 2012). Our recent work at the genetic and neuroanatomical levels revealed that different hippocampal regions mature at different times during development (Favre, Banta Lavenex, & Lavenex, 2012a, 2012bJabès, Banta Lavenex, Amaral, & Lavenex, 2010Lavenex, Banta Lavenex, & Amaral, 2007;Lavenex, Sugden, Davis, Gregg, & Banta Lavenex, 2011). These findings, together with our studies of the development of human spatial memory (Ribordy, Jabès, Banta Lavenex, & Lavenex, 2013;Ribordy Lambert, Lavenex & Banta Lavenex, 2015), support the hypothesis that the differential maturation of distinct hippocampal circuits might underlie the differential emergence of specific ''hippocampus-dependent'' memory processes, culminating in the emergence of adult-like episodic memory concomitant with the maturation of all hippocampal circuits .…”
Section: Hippocampusmentioning
confidence: 99%